Limits to Performance - Women's NCAA Championships - Sands, W. A.; McNeal, J. R. (Technique, 2000)
In searching for a means of understanding the overall development of gymnastics, and insight into where the sport may be going in the near future, we undertook to determine the trends of performance in women's collegiate gymnastics. Because the NCAA maintains good records, the size and conduct of the competitions are relatively stable, and the increasing performance level of collegiate gymnasts has been obvious, these data were particularly attractive for study.